An Hybrid Coding Technique for Efficient Bandwidth Usage in conformity with IEEE 802.11 WLAN Standard - Isiaka Ajewale Alimi; Kayode Francis Akingbad; Jide Julius Popoolae; Michael O. Kolawole (International Journal of Electrical and Computer Engineering (IJECE), 2013)
The contemporary Wireless Local Area Networks (WLANs) systems like IEEE 802.11a/g standards use Coded Orthogonal Frequency Division Multiplexing (COFDM) and offer data rates of up to 54 Mbps at 2.4 GHz or 5 GHz. IEEE 802.11n is a recent WLAN standard capable of not only providing increased data rate and improved range but also reduced signal fading. These benefits are achieved through the use of space-time coded Multiple-Input, Multiple-Output with Orthogonal Frequency Division Multiplexing (MIMO-OFDM) technique which provides the possibility of increased signal strength at the receiver with optimal bandwidth and power efficiency. In this paper, a novel hybrid space-time block coding (HSTBC) scheme is proposed for mitigating signal fading as well as enhancing the performance of MIMO–OFDM based WLANs. The signal to be transmitted is first pre-coded and the resulting output is then coded using space-time block code to form a HSTBC. Simulation results show that the HSTBC scheme considerably reduced the effect of multipath fading in wireless communication systems with improved bit error rate. Our proposed HSTBC improves the performance of the system in terms of data transmission as the capacity of the system almost doubled the capacity of a conventional STBC system.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3668